Roles of Advisory Councils in Urban Governance - Pawłowska, Agnieszka (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2023)
Urban governance (UG) is a place-based network of cooperation between public and non-public actors where public authorities play a strategic role in deciding on city matters. A number of UG actors include advisory councils (ACs), characterized by a long tradition, universality, stability and objectives related to urban affairs. The article aims to identify AC roles in UG. In addition, the author hypothesizes a correlation between the number of official (statutory) and informal (not legally regulated) roles and differences between ACs in terms of the roles they play. The hypotheses were verified in qualitative research. 57 semi-structured interviews were conducted with members of the youth councils, senior citizen councils, sport councils, and councils for residents with disabilities in 16 Polish cities. The interview transcripts were uploaded to QDA Miner for encoding and analysis. It was found that all ACs, regardless of their official roles, play informal roles, and all these roles are related to UG. There is no correlation between the number of official and informal roles, which would make ACs very similar unless the mandatory character of the roles played by the council for residents with disabilities, which differs this AC from the other. The results of the study lead the author to recommend revisions to AC regulations in order to increase their participation in the UG.

Współrządzenie miastem (WM) to związana z miejscem sieć współpracy między podmiotami publicznymi i niepublicznymi, w której władze publiczne odgrywają strategiczną rolę w podejmowaniu decyzji o sprawach miasta. Wśród aktorów WM są rady społeczne (RS), które charakteryzują się długą tradycją, powszechnością, stabilnością i celami związanymi z miastem. Artykuł ma na celu identyfikację ról RS w WM. Ponadto autorka stawia hipotezę o związku między liczbą ról oficjalnych (ustawowych) i nieformalnych (nieuregulowanych prawnie) oraz o różnicach między RS pod względem pełnionych ról. Hipotezy zweryfikowano w badaniach jakościowych. Przeprowadzono 57 wywiadów częściowo ustrukturyzowanych z członkami rad młodzieżowych, rad seniorów, rad sportu i rad ds. osób niepełnosprawnych w 16 polskich miastach. Transkrypcje wywiadów zostały wprowadzone do QDA Miner w celu zakodowania i analizy. Stwierdzono, że wszystkie RS, niezależnie od swoich ról oficjalnych, pełnią role nieformalne, a wszystkie te role są związane z WM. Nie ma związku między liczbą ról oficjalnych i nieformalnych, co sprawia, że RS wydałyby się bardzo podobne, gdyby nie role pełnione przez radę ds. osób niepełnosprawnych, które mają charakter obowiązku ustawowego, co istotnie różni tę radę od pozostałych. Wyniki badań skłoniły autorkę do zaproponowania zmian w przepisach dotyczących RS w kierunku zwiększenia ich udziału w UG.
Role rad społecznych we współrządzeniu miastem
Keywords: advisory council; social council; city; role; urban governance; Poland; rada doradcza; rada społeczna; rola; współrządzenie miastem; Polska